2020
DOI: 10.1016/j.atherosclerosis.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of human immunodeficiency virus and hepatitis C virus infection with long-term outcomes post-ST segment elevation myocardial infarction in a disadvantaged urban community

Abstract: Background: HIV and HCV have been linked to an increased risk of cardiovascular disease (CVD). Their impact on long-term outcomes following ST-segment myocardial infarction (STEMI) has not been previously studied. Methods:We leveraged data from a STEMI registry (n=1208) at an inner-city health system to assess the influence of HIV and HCV on post-STEMI outcomes. Cox regression was used to compare HIV-monoinfected (n=22), HCV-monoinfected (n=26) and HIV-HCV-coinfected patients (n=8) with the neither-infected gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 36 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Of note, our study found suboptimal statin prescription in patients living with HIV after ACS or revascularization, which is consistent with results of other retrospective studies. 11,18,19,26,28,[38][39][40][41][42] These findings and those of the Evaluating the Use of Pitavastatin to Reduce the Risk of Cardiovascular Disease in HIV-Infected Adults (REPRIEVE) trial, 14 which demonstrated the benefits of pitavastatin for primary prevention of atherosclerotic cardiovascular disease among patients living with HIV, highlight the need for a concerted effort to improve guideline-directed statin prescription and adherence among these patients. 43 Additionally, the higher prevalence of smoking and higher triglyceride levels we found among patients living with HIV highlight areas for optimization, with the goal of improving secondary prevention of atherosclerotic cardiovascular disease.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Of note, our study found suboptimal statin prescription in patients living with HIV after ACS or revascularization, which is consistent with results of other retrospective studies. 11,18,19,26,28,[38][39][40][41][42] These findings and those of the Evaluating the Use of Pitavastatin to Reduce the Risk of Cardiovascular Disease in HIV-Infected Adults (REPRIEVE) trial, 14 which demonstrated the benefits of pitavastatin for primary prevention of atherosclerotic cardiovascular disease among patients living with HIV, highlight the need for a concerted effort to improve guideline-directed statin prescription and adherence among these patients. 43 Additionally, the higher prevalence of smoking and higher triglyceride levels we found among patients living with HIV highlight areas for optimization, with the goal of improving secondary prevention of atherosclerotic cardiovascular disease.…”
Section: Discussionmentioning
confidence: 94%
“…30,31 All were retrospective cohort studies except for 3 prospective studies (Table 1). 11,26,30 Details of patient characteristics and outcomes by study are presented in Table 1 high-density lipoprotein cholesterol (40 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] vs 46 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] mg/dL; P = .03) levels. (To convert triglycerides and cholesterol to millimoles per liter, multiply by 0.0113 and 0.0259, respectively.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We divided the cohort into neither-infected, HCV-monoinfected, HIV-monoinfected and HIV--HCV-coinfected groups, as done elsewhere [30]. We employed relative risk regression using a Poisson working model with a log-link function and robust standard errors to calculate risk ratios of new-onset LV dysfunction with the neither-infected group as referent.…”
Section: Methodsmentioning
confidence: 99%